Identifikasi Trenggiling (Manis javanica) Menggunakan Penanda Cytochrome B Mitokondria DNA (IDENTIFICATION OF PANGOLIN (MANIS JAVANICA DESMAREST, 1822) USING CYTOCHROME B mtDNA MARKER) - ., Wirdateti; Semiadi, Gono; ., Yulianto (Jurnal Veteriner, 2013)
The aim of this study was to identify the gentic profile of Malay pangolin (Manis javanica) and originpatterns of confiscated specimens.  Tissue samples of Malay pangolin were collected from several confiscatedmaterials in Tangerang, Medan, and Lampung. Wild collections tissue were also conducted in Lampungand Sukabumi. The study was conducted using  conserved Cytochrome b (Cyt. B) DNA mitochondria(mtDNA). The results showed that based on nucleotide base lentgh of 420 nt, confiscated pangolin wasdistributed in three clades and two groups. Haplotype variations was high, consisted of 19 haplotypes in19 individuals (TR1-TR19). On fisrt clade (TR4,7,16,9,19) high substitution occured in adenin base, cladetwo (TR14,17,1,2,15,3,8,13) high substitution occured in guanin base and clade three  (TR5,6,10,11,12) incytosin. It was concluded that haplotipe variation of each populations  was high and for genetic distancebetween individuals was low. Mutation rates was dominated by transition  from guanine to adenine
Keywords: Malay pangolin, Manis javanica, smuggling, cytB mtDNA